The influence of English songs on students’ spelling accuracy - Rezza Fatwassani; Nur Azmi Rohimajaya; Aisyah Hafshah Saffura El-Muslimah; Welliam Hamer; Nadiah Ma'mun (Early Publishing Group, 2025)
This study investigates the influence of English songs on students’ spelling accuracy, a crucial component of effective written communication in language learning. As traditional spelling instruction often lacks engagement and contextual relevance, exploring innovative methods to enhance spelling skills is essential. While previous research has highlighted the benefits of songs for vocabulary acquisition, pronunciation, and motivation, limited attention has been given to their direct impact on spelling proficiency. The aim of this study is to explore how English songs support the development of accurate spelling among EFL learners and to identify the underlying mechanisms involved. Adopting an exploratory research design, the study involved 27 eleventh-grade students from a senior high school in Indonesia with intermediate English proficiency. Data collection comprised semi-structured interviews and reflective journal entries, allowing for a comprehensive understanding of students’ perceptions and experiences related to song-based spelling practice. Data analysis involved thematic coding to identify recurring patterns and insights concerning the cognitive and affective processes that facilitate spelling improvement through musical input. The findings reveal that songs contribute to spelling accuracy by reinforcing visual and auditory memory, providing repetitive exposure to correct spelling patterns, fostering motivation and engagement, and encouraging autonomous learning. Students reported increased confidence, better retention of spelling patterns, and heightened curiosity about unfamiliar words. The implications of this research highlight the pedagogical potential of integrating English songs into spelling instruction, offering an engaging, multimodal approach that supports both cognitive and emotional learning dimensions. The study suggests that utilizing music not only enhances language motivation but also provides a meaningful context for internalizing correct spelling, thereby contributing to more effective literacy development in EFL settings.